Odpowiedzi

2009-11-30T19:57:44+01:00
A)
2 (x - ½) - x + 3 = 3
2x-1-x+3=3
x+2=3
x=3-2
x=1
------------------
b)
0 = 3 - (2x + 1)
0=3-2x-1
0=2-2x
2x=2
x=1
-------------------------
c)
0 = (x - 1) - (3x - 5)
0=x-1-3x+5
0=-2x+4
2x=4
x=2
--------------------
d)
(-½x + 1) + 3x/2 = 3
-½x + 1 + 3x/2 = 3
x+1=3
x=3-1
x=2
-------------------------
e)
3(1 - x) - (1 - 2x) = 9
3-3x-1+2x=9
-x+2=9
-x=9-2
-x=7 /*(-1)
x=-7
--------------------------------------
f)
0,5 (2 - 4x) = 3 - x
1-2x=3-x
-2x+x=3-1
-x=2 /*(-1)
x=-2
2009-11-30T20:07:01+01:00
A)2 (x - ½) - x + 3 = 3
2x-1-x+3=3
x+2=3
x=1
b) 0 = 3 - (2x + 1)
0=3-2x-1
0=2-2x
2x=2|:2
x=1
c)0 = (x - 1) - (3x - 5)
0=x-1-3x+5
0=-2x+4
2x=4|:2
x=2
d)(-½x + 1) + 3x/2 = 3
-½x + 1+1½x=3
x+1=3
x=2
e) 3(1 - x) - (1 - 2x) = 9
3-3x-1+2x=9
-x=7|×(-1)
x=-7
f)0,5 (2 - 4x) = 3 - x
1-2x=3-x
-x=2|×(-1)
x=-2